Pengaruh Perceived Usefullnes, Perceived Ease Of Use terhadap Online Purchase Intention melalui Perceived Customer Value pada Online Shoping SHOPEE - Westi Kurnia Ningrum (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
Online purchase intention is important because it can increase company profit. The study was conducted to determine the effect of perceived usefullnes, perceived ease of use, on oline purchase intention throuh perceived customer value in Online Shoping SHOPEE. The research was conducted at the Yogyakarta, samples taken as many as 100 people with accidental sampling method. The data collection is done by distributing questionnaires using a scale of 1-5 points to measure 20 indicators. The results of this study indicate the results for the variable perceived usefullnes positive effect on online purchase intention, perceived ease of use positive effect on online purchase intention,variable perceived usefullnes positive effect on perceived customer value, variable perceived ease of use positive effect on perceived customer valueand perceived customer value positive effect on online purchase intention. For the determinantion of the results of this test is model I 72,2% on online purchase intention intention and model II 63,3% on perceived customer value.